The long-term impact of the MEMA kwa Vijana adolescent sexual and reproductive health intervention: effect of dose and time since intervention exposure. - Aoife M Doyle; Helen A Weiss; Kaballa Maganja; Saidi Kapiga; Sheena McCormack; Deborah Watson-Jones; John Changalucha; Richard J Hayes; David A Ross (PLoS ONE)
Background Despite recent decreases in HIV incidence in many sub-Saharan African countries, there is little evidence that specific behavioural interventions have led to a reduction in HIV among young people. Further and wider-scale decreases in HIV require better understanding of when behaviour change occurs and why. The MEMA kwa Vijana adolescent sexual and reproductive health intervention has been implemented in rural Mwanza, Tanzania since 1999. A long-term evaluation in 2007/8 found that the intervention improved knowledge, attitudes to sex and some reported risk behaviours, but not HIV or HSV2 prevalence. The aim of this paper was to assess the differential impact of the intervention according to gender, age, marital status, number of years of exposure and time since last exposure to the intervention. Methods In 2007, a cross-sectional survey was conducted in the 20 trial communities among 13,814 young people (15-30 yrs) who had attended intervention or comparison schools between 1999 and 2002. Outcomes for which the intervention had an impact in 2001 or 2007 were included in this subgroup analysis. Data were analysed using cluster-level methods for stratified cluster-randomised trials, using interaction tests to determine if intervention impact differed by subgroup. Results Taking into account multiplicity of testing, concurrence with a priori hypotheses and consistency within the results no strong effect-modifiers emerged. Impact on pregnancy knowledge and reported attitudes to sex increased with years of exposure to high-quality intervention. Conclusions The desirable long-term impact of the MEMA kwa Vijana intervention did not vary greatly according to the subgroups examined. This suggests that the intervention can have an impact on a broad cross-section of young people in rural Mwanza. Trial registration ClinicalTrials.gov NCT00248469.